Effect of sense of self on nonsuicidal self-injury in college students: a regulated mediating model - Yang Li; Fangzhao Xu; Zeng Yi; Fan Ou; Shanshan Tao; Xiaoling He (BMC, 2024)
Abstract Objective This study aims to examine the relationship and mechanism between sense of self and nonsuicidal self-injury among college students, providing a new theoretical basis for predicting and preventing such behavior. Methods A total of 1350 college students completed the Sense of Self scale, nonsuicidal self-injury questionnaire, frustration scale, and social problem-solving questionnaire. Results (1) Negative Sense of Self predicts frustration, and frustration positively predicts nonsuicidal self-injury. (2) Frustration serves as a partial mediator in the relationship between sense of self and nonsuicidal self-injury. (3) The impulsive-negligent social problem-solving style regulates the first half of the mediation model by influencing the relationship between sense of self and frustration. Conclusion Frustration, mediated by sense of self, increases the risk of nonsuicidal self-injury, and this relationship is moderated by the impulsive-negligent social problem-solving style. Sense of Self is a necessary but not sufficient condition for nonsuicidal self-injury, indirectly influencing such behavior through frustration triggered by stress events.